2022
DOI: 10.48550/arxiv.2208.06760
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electroweak precision tests for triplet scalars

Abstract: Electroweak precision observables are fundamentally important for testing the standard model (SM) or its extensions. The influences to observables from new physics within the electroweak sector can be expressed in terms of oblique parameters S, T, U. The recently reported W mass excess anomaly by CDF modifies these parameters in a significant way. By performing the global fit with the CDF new W mass measurement data, we obtain S = 0.03 ± 0.03, T = 0.06 ± 0.02 and U = 0.16 ± 0.03 (or S = 0.14 ± 0.03, T = 0.24 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 98 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…Moreover, the new observation has a 7σ deviation from the SM prediction m W = 80.361 GeV [74]. If the W -mass anomaly is confirmed by the measurements at the LHC with more cumulative data, it would be a solid piece of evidence that exhibits the effects of new physics [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: Introductionmentioning
confidence: 65%
“…Moreover, the new observation has a 7σ deviation from the SM prediction m W = 80.361 GeV [74]. If the W -mass anomaly is confirmed by the measurements at the LHC with more cumulative data, it would be a solid piece of evidence that exhibits the effects of new physics [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: Introductionmentioning
confidence: 65%
“…We note that Ref. [94] studied the compatibility of the spectrum preferred by the CDF II W mass with other EWPOs and Higgs precision data in an inert complex triplet extension (with hypercharge ) of the SM, and Ref. [95] studied both complex and real triplet extensions by directly performing a global fit to EWPOs with CDF II via Bayesian analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, Refs. [76][77][78][79] have demonstrated that the recently reported measurement of the W -bosoon mass by the CDF experiment [80] which substantially differs from the global EW fit [81] can be explained within the type-II see-saw model predicting such low-mass H ±± and slightly heavier singly-charged and neutral scalars. Therefore, it is paramount to look for such H ±± at the LHC.…”
Section: Introductionmentioning
confidence: 91%